Cash Recovery Rates and Measures of Firm Profitability. - Salamon, Gerald L. (The Accounting Review, 1982)
ABSTRACT: Previous analytical work has shown that a firm's cash recovery rate (the ratio of cash recovery during a period to gross investments outstanding during the period) is related to the internal rate of return of firm projects in the event that the firm reinvests all of its cash flows. This paper extends the previous analytical work by establishing a link between a firm's cash recovery rate and the internal rate of return of firm projects in circumstances when the firm does not reinvest all of its cash flows. Additionally, this paper applies the extended model to a group of firms in order to obtain estimates of their internal rates of return. Work of this kind would seem to be of particular interest to economic researchers who are interested in theoretically defensible empirical measures of firm profitability.